Productivity, efficiency and gender equity of community mobilisation approaches in trichiasis campaigns: analysis of programmatic data from seven sub-Saharan African countries. (6th April 2022) - ul Hassan, Ehtisham; Kelly, Michaela; Waititu, Titus; Olobio, Nicholas; Kabona, George; Mkocha, Harran; Kivumbi, Peter; Mwale, Consity; Mubangizi, Alfred; Mugume, Francis; Baayenda, Gilbert; Mayeku, Robert; et al.
Abstract: Background: Achieving elimination of trachoma as a public health problem in trichiasis-endemic districts requires a systematic approach to trichiasis case finding and outreach. Methods: Programme monitoring data from seven countries for 2017–2019 were used to explore the efficiency of different community mobilisation approaches and uptake of trichiasis surgical services. Results: Three countries (Ethiopia, Kenya and Mozambique) using broad-based community mobilisation strategies had large numbers of people presenting at outreach but only 2.9% of them had trichiasis, while in four countries (Nigeria, Tanzania, Uganda and Zambia) using house-to-house case finding, 37.5% of outreach attendees had trichiasis. Countries using house-to-house case finding have proportionally more women attending outreach compared with countries using broad-based mobilisation. Among trichiasis cases offered surgery 86% accepted, which was similar for men and women. Conclusions: In these settings, house-to-house case finding appears to be a more effective and efficient approach to ensure that trichiasis cases, particularly in women, obtain access to surgical services.